The North of Lisbon Region: a Dynamic Landscape - Zêzere, José Luís (2021)
The alternating lithology together with the low-to-moderate monocline south to southeast dipping in the North of Lisbon Region promoted the development of cuesta landforms that were shaped by differential erosion during the Quaternary. The fluvial erosion generated a large depression—the Loures Basin—where several deposits were formed during the Quaternary. The oldest terrace testifies a paleo-drainage towards NE, and the present-day organization of the fluvial system was marked by the stream piracy in the terminal zone of the Trancão River. In the north part of the Loures Basin, a debris flow deposit is conserved and it is probably related to the rupture zone of an old slope movement identified by Ferreira in 1984. This feature is the oldest evidence of slope instability in the region. More recently, in November 1755, the Lisbon earthquake generated rockfalls along the larger fluvial valley in the area—the Trancão River valley. The recent and present-day slope instability have been characterized by the occurrence of rainfall-triggered shallow slides and deep-seated slope movements. Shallow slides have been triggered by intense rainfall events, whereas deep-seated slope movements have been associated to long-lasting rainfall events.